Influence of institutional transformation in agricultural sector of Russia on small businesses (organizations) - G. N. Ryazanova; S. L. Sazanova (Путеводитель предпринимателя)
The article examines a set of agrarian policy measures that contribute the formation of institutional conditions for the development of small enterprises in the agrarian sector of the Russian economy. The authors identify the regulatory, financial and administrative tools of state regulation of the agricultural sector in Russia and analyze the results of the impact of institutional transformations on microeconomic agents of small and medium businesses.